Implementation of Al-Qur'an Literacy for High School Students - Hatika Hatika; M. Zuhri Abu Nawas; Mardi Takwim; A. Riawarda (Journal of Indonesian Islamic Studies, 2021)
The aims of this study were to: 1) To obtain a clear picture of the implementation of Al-Qur'an literacy in SMA Negeri 8 North Luwu Regency 2). Knowing the Literacy level of reading the Qur'an of Students at SMA Negeri 8 North Luwu Regency, 3) Identifying Supporting and Inhibiting Factors for the Success of Implementing Al-Qur'an literacy at UPT SMA Negeri 8 North Luwu Regency. This research is qualitative research that uses a normative pedagogical, sociological, and theological approach. The subjects of this study consisted of the Principal 2) Teacher 3) Coach, and Students, SMA Negeri 8 Luwu Utara. Data analysis in qualitative research generally begins with data collection, data reduction, data presentation, and conclusion drawing. The results of the research and analysis concluded as follows.